2000
DOI: 10.1097/00005537-200006000-00001
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art Review: Current Status of Topical Nasal Antimicrobial Agents

Abstract: The nasal cavity and paranasal sinuses are probably one of the last frontiers in the head and neck region where the use of topical antimicrobial agents is not yet established. Although the anatomy of the nasal cavity and the paranasal sinuses can theoretically be exploited for the administration of antimicrobials in rhinosinusitis, very few studies have been conducted to test the feasibility of this mode of therapy. We review the anatomical and physiological factors that should be considered in the use of topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…In CRS though, the chronic infection impairs the ciliary function, in favor of the prolonged residence of topically delivered medications. On the other hand, it is suggested that the active transfer of medications to the choanae might actually enhance their distribution to remote mucosal subsites (Goh and Goode, 2000).…”
Section: Micro-anatomymentioning
confidence: 99%
“…In CRS though, the chronic infection impairs the ciliary function, in favor of the prolonged residence of topically delivered medications. On the other hand, it is suggested that the active transfer of medications to the choanae might actually enhance their distribution to remote mucosal subsites (Goh and Goode, 2000).…”
Section: Micro-anatomymentioning
confidence: 99%
“…Although oral and intravenous deliveries consistently achieve the therapeutic minimum inhibitory concentration (MIC) for the common pathogens of CRS in the sinonasal mucosa [46,47], topical administrations can localize drug delivery to the sinonasal cavity and minimize the systemic effects of the antibiotics [48,49]. Although oral and intravenous deliveries consistently achieve the therapeutic minimum inhibitory concentration (MIC) for the common pathogens of CRS in the sinonasal mucosa [46,47], topical administrations can localize drug delivery to the sinonasal cavity and minimize the systemic effects of the antibiotics [48,49].…”
Section: Topical Antibiotic Therapymentioning
confidence: 99%
“…In addition, several studies have shown that prophylactic use of mupirocin ointment within the nasal cavity in S. aureus carriers decreases the risk of infection of the surgical site, alleviate problems in ICU patients, who undergo intubation for a long duration [3,4,[10][11][12]. However, except for the study by Takahashi S et al, no comprehensive study has been carried out to evaluate the efficacy of this ointment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in case of favourable effects this ointment can be used in all the surgeries that are associated with nasal intubation to decrease the complications of the procedure, especially in compromised patients. It should be pointed out that no studies to date have reported any major side effects associated with the use of mupirocin ointment and the complications have been confined to minor irritation of the nasal mucosa that is resolved after discontinuation of the use of the ointment [4,10].…”
Section: Introductionmentioning
confidence: 99%